A syntactical comparative analysis of the spatial properties of Prairie style and Victorian domestic architecture. Issue 3 (2nd April 2016) - Amini Behbahani, Peiman; Ostwald, Michael J.; Gu, Ning
Abstract : Frank Lloyd Wright's Prairie houses have been repeatedly praised for introducing a number of innovations in domestic spatial planning. In particular, historians and critics have identified the spatial properties of 'holism', 'inwardness' and 'circularity' as signalling a clear departure from the spatial characteristics of Victorian architecture. However, despite these claims, the actual spatial differences between the Prairie houses and Victorian houses have never been quantified. Are Wright's Prairie houses really so different from the Victorian houses which were being constructed at the same time? This paper presents the results of a comparative computational analysis of four specific spatial qualities of Prairie and Victorian architecture. Using Space Syntax techniques, the paper analyses the plans of forty-two houses. The results suggest that, within the limits of the methods used, the Prairie houses were not so inventive as previously claimed. Nevertheless, the paper also identifies possibilities for alternative interpretations of the results that might begin to explain the accepted position.